(untitled) (Latakia University Journal -Basic Sciences Series, 2021)
The aim of this research is to present exact analytical solutions for generalized Benjamin-Bona-Mahony equation with time-dependent coefficients in variant exponent (positive, negative). The sine-cosine method and solitary wave ansatz method are used. The study is characterized by variety of exact explicit solutions: periodic, compactons, solitary patterns, bright soliton. Necessary conditions for existence of this solutions are presented.